Common path optical coherence tomography with electronic feedback for improved sensitivity - Alsnaie, Khalid (Oficyna Wydawnicza Politechniki Wrocławskiej, 2023)
Optical coherence tomography (OCT) imaging has become a useful tool in medical diagnosis over the past 25 years, because of its ability to visualize intracellular structures at high resolution. The main objective of this work is to add electronic feedback to the optical coherence tomography setup to increase its sensitivity. Noise added to the measured interferogram obscures some details of examined tissue layered structure. Adjusting signal power level in such a way to improve signal-to-noise ratio can help to enhance image quality. Electronic feedback is added to enhance system sensitivity. A logarithmic amplifier is included in the OCT setup to automatically adapt signal level. Moreover, the resolution of the optical spectrum analyzer is controlled according to the farthest layer detected in the A-scan. These techniques are tested showing an improvement in obtained image of a human nail.
Optica Applicata, Vol. 53, 2023, nr 3, s. 495-504
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; optical coherence tomography (OCT); frequency domain OCT; medical imaging; partially coherent interferometers; B-scan